Relazioni tra il lessico e la sintassi: classi aspettuali di verbi ed il passivo spagnolo - de Miguel, Elena (Círculo de Lingüística Aplicada a la Comunicación, 2023)
The aim of this article is to examine the different restrictions (especially those of aspectual nature) that constrain the process of passive formation in Spanish. The proposal defended here is based on the idea that verbal predicates denote events that include internal (subeventual) structure and, specifically, that there are eight different classes of verbs which can be distinguished according to their phase-structure, as has been proposed, for independent reasons, in previous work ― see, e.g., (Fernández Lagunilla and de Miguel, 1999) and (De Miguel and Fernández Lagunilla, 2000). The formation of passive structures is a sublexically oriented process. Each of the three types of passive constructions in Spanish (ser + past participle, se + active verb and estar + past participle) selects a certain phase of the internal (subeventual) structure of the verb, in complementary distribution. In this way, we can explain the apparent chaos of lexical and syntactic restrictions in the Spanish passive.